Traumatic popliteal artery spasm diagnosed using intraoperative angiography: A case report - Yuta Izawa; Kazuo Sato; Yoshihiko Tsuchida (Trauma Case Reports, 2023)
There are few reports of traumatic arterial spasm in large-sized vessels in the extremities, and many surgeons are skeptical of its existence. We report a case of traumatic popliteal artery injury (PAI), which was later diagnosed as traumatic popliteal artery spasm on intraoperative angiography.A male patient, aged 54 years, was injured when a heavy object weighing approximately 100 kg fell on his right knee. Three hours after the injury, the patient was transported to our trauma center. The dorsalis pedis and posterior tibial arteries were not palpable, and his right lower leg was cold. However, he could move his ankle and toes completely and had no numbness or paresthesia in his right lower limb. Computed tomography angiography showed an interruption of the popliteal artery at the knee joint level and an enhancement on the distal side of the injury site. We diagnosed lower limb ischemia resulting from PAI and operated for revascularization.Under general anesthesia, the popliteal artery was explored via a posterior S-shaped incision in the prone position. No arterial abnormalities were observed macroscopically, and the injured area remained unidentified. Therefore, a contrast medium was injected into the popliteal artery using a 20-gauge intravascular needle, and angiography was performed, which revealed that the popliteal artery was patent; however, there was circumferential arterial stenosis at the level of the knee joint. At this point, the right lower limb's coldness had disappeared. Arterial spasm was speculated to cause the transient popliteal occlusion and lower leg ischemia.Immediate revascularization should be attempted when PAI is suspected. If no gross vascular abnormalities are confirmed, intraoperative angiography is useful for diagnosing arterial spasm.